2011
DOI: 10.1109/jstqe.2010.2070790
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Phases in III--V Nanowires: From Random Toward Engineered Polytypism

Abstract: Recent relationships between Papua New Guinea (PNG), the International Monetary Fund (IMF), and the World Bank have been stormy. At various points in the loan negotiations students rioted, the Prime Minister told the World Bank to 'go to hell', and the World Bank's chief negotiator defected to the PNG side. He was later jailed. The relationship between the Asian Development Bank (ADB) and its South Pacific clients were also sometimes uneasy, and led its Board of Directors to commission a self-assessment (Knapm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
211
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(220 citation statements)
references
References 143 publications
7
211
0
2
Order By: Relevance
“…It has been observed that the III-V semiconductors can often adopt a different crystal phase than in bulk when grown as NWs. For instance, GaP, GaAs, InP and InAs were found to change their crystal phase from ZB in bulk to WZ in Au-catalyzed NWs grown by MOVPE [62,106]. In the case of Au-catalyzed MBE, the GaAs NWs usually adopt the WZ phase [64,97,107], whereas the self-catalyzed GaAs NWs are usually ZB [108][109][110].…”
Section: Extended Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the III-V semiconductors can often adopt a different crystal phase than in bulk when grown as NWs. For instance, GaP, GaAs, InP and InAs were found to change their crystal phase from ZB in bulk to WZ in Au-catalyzed NWs grown by MOVPE [62,106]. In the case of Au-catalyzed MBE, the GaAs NWs usually adopt the WZ phase [64,97,107], whereas the self-catalyzed GaAs NWs are usually ZB [108][109][110].…”
Section: Extended Defectsmentioning
confidence: 99%
“…However in other reports, it has been argued that the sequence should be repeated at least for four bilayers, i.e. CACA and ABCA before they can be considered as WZ and ZB segments, respectively [106]. Nevertheless, these structural defects or the mixed ZB-WZ structures can be unwanted as they have reported to influence the optical and transport properties of the NWs [43,122].…”
Section: Extended Defectsmentioning
confidence: 99%
“…Occasionally, NW segments of hexagonal wurtzite (WZ) structure have been observed to penetrate the ZB structure, as well. In III-V NWs structural defects, such as rotational twins and stacking faults (SFs) along the growth direction of the NWs are often observed, the latter been responsible for the transition between ZB and WZ structures and viceversa [14,15]. High density of these defects in the nanometer scale may induce a variation of the band gap and influence electron transport along the NWs [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the values of the effective g-factors are often determined as g = (E + (B) − E − (B))/µ B B, where E ± (B) is the energy of opposite spin projections under a magnetic field B. We have calculated the g factor at B = 1 T switching on and off the spin-orbit term ∆ in Hamiltonian (7). This leads to g factors with enabled (g so ) and suppressed (g 0 ) spin mixing.…”
Section: B Holesmentioning
confidence: 99%